2018
DOI: 10.1016/j.neuroimage.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally-invariant mapping of scalar and orientational metrics of neuronal microstructure with diffusion MRI

Abstract: We develop a general analytical and numerical framework for estimating intra- and extra-neurite water fractions and diffusion coefficients, as well as neurite orientational dispersion, in each imaging voxel. By employing a set of rotational invariants and their expansion in the powers of diffusion weighting, we analytically uncover the nontrivial topology of the parameter estimation landscape, showing that multiple branches of parameters describe the measurement almost equally well, with only one of them corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
369
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 201 publications
(403 citation statements)
references
References 87 publications
(194 reference statements)
29
369
5
Order By: Relevance
“…The decision to fix the axial intra- and extra-axonal diffusivities equal to one another is another assumption that can lead to unpredictable effects. Recent work has shown that fixing D a,‖ = D e,‖ masks a fundamental property of multi-compartment models, namely the multiplicity of mathematical solutions (Jelescu et al, 2016a; Novikov et al, 2016b). Indeed, it has been shown that, if all parameters in the fitting procedure are released, namely f intra , D a,‖ , D e,‖ , D e,⊥ and κ (ignoring the CSF compartment), there are two distinct solutions to the parameter estimation problem, both within biologically plausible ranges (Figure 2).…”
Section: Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decision to fix the axial intra- and extra-axonal diffusivities equal to one another is another assumption that can lead to unpredictable effects. Recent work has shown that fixing D a,‖ = D e,‖ masks a fundamental property of multi-compartment models, namely the multiplicity of mathematical solutions (Jelescu et al, 2016a; Novikov et al, 2016b). Indeed, it has been shown that, if all parameters in the fitting procedure are released, namely f intra , D a,‖ , D e,‖ , D e,⊥ and κ (ignoring the CSF compartment), there are two distinct solutions to the parameter estimation problem, both within biologically plausible ranges (Figure 2).…”
Section: Modelsmentioning
confidence: 99%
“…Recently, (Novikov et al, 2016b) and (Reisert et al, 2017) have exploited this property to estimate the scalar parameters of a two-compartment kernel separately from the ODF: 𝒦false(b,boldg·boldnfalse)=fintraebDnormala,false‖false(boldg·boldnfalse)2+false(1fintrafalse)ebDnormale,false‖false(boldg·boldnfalse)2bDnormale,false(1false(boldg·boldnfalse)2false)…”
Section: Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameters are estimated by fitting dMRI data, often using nonlinear optimization methods. In WM, one such parameter, intrinsic intra‐axonal diffusivity ( D a ), has proven especially challenging to measure . This is because D a estimates are sensitive to modeling assumptions and tend to be only loosely constrained by the data, although some recently proposed approaches seem to be more promising …”
Section: Introductionmentioning
confidence: 99%